Effects of an Applied Local Dance Program on Physical Fitness in Older Adults at Huai Yang Sub-District Khong, Chiam District in Ubonratchathani Province - Sooktho, Suparat; Junlatat, Jintana; Sangprapai, Warinee; Kamuttachat, Phanida; Thorajak, Piyaporn; Koedsuk, Chantarat; Homwan, Saowakhon; Lunbappa, Nicha (Health Science Journal of Thailand, 2025)
Older adults are in a stage where the efficiency of various organs decreases. There are problems with joint mobility, and muscle strength decreases, which affects imbalance. This one-group pretest-posttest design aimed to examine the effects of an applied local dance program on the physical fitness of older adults. The participants were 28 older adults living in Huai Yang Sub-district, Khong Chiam District, Ubon Ratchathani Province, who received the applied local dance program of 14 postures for 40 minutes per day, three days a week for 8 consecutive weeks. There were three physical fitness outcomes in this study, which were recorded at baseline week 4 and at the end of study (week 8), including a leg muscle strength test, lower back, and posterior thigh muscle flexibility and dynamic balance test. The results found that the leg muscle strength test and lower back, and posterior thigh muscle flexibility were statistically significant improvements (p-value <0.05) at week 4 and week 8. For the dynamic balance test, tended to improve at week 4 and found that there were statistically significant improvements (p-value <0.05) at week 8. This study indicates that the 14 postures in the applied local dance program can promote improved physical fitness in older adults.